(untitled) (Archives of Mechanics - Test, 2002)
This paper deals with the interaction of thermal radiation with free convection, laminar boundary-layer flow past a heated rotating axisymmetric round-nosed body of uniform surface temperature. The fluid considered is a gray, absorbing-emitting but nonscattering medium, and Rosseland approximation is used to describe the radiative heat flux. The difficulty of having a unified mathematical treatment of this problem is due to the nonsimilarity nature of the governing equations arising from the buoyant force-field and the transverse curvature of the body. The important parameters of this problem are the Planck number, Rd, the buoyancy parameter, λ, and the wall to free stream temperature ratio, θw. Numerical solution of the boundary-layer equations are performed using the Keller-box method as well as the local nonsimilarity method. The theory is applied to a rotating hemisphere for a gas with Prandtl number of 0.72. The effects of the parameters λ, Rd and θw are shown on the velocity and temperature profiles, as well as on the local skin friction coefficient and local rate of heat transfer.